EVALUASI PEMBERIAN PENYULUHAN PADA PENGETAHUAN WANITA USIA SUBUR TENTANG IVA TEST - Sophia (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2021)
ABSTRACT The incidence of cervical cancer is 0.8%, making it the type of cancer with the highest prevalence in Indonesia. One of these circumstances is influenced by the lack of knowledge of women of childbearing age (WUS) about cervical cancer, especially early detection with the IVA test. The provision of health education such as counseling is very important. The results of the preliminary study show that 6 out of 10 WUS people in Central Cimahi do not know about the IVA Test. The purpose of this study was to determine the evaluation of the provision of counseling on WUS knowledge about the IVA Test at the Cimahi Tengah Health Center in February 2019. The research method used was analytic with a cross sectional design. The research sample is WUS who are married at the Puskesmas Cimahi Tengah as many as 98 people taken by means of quota sampling. Collecting data using a questionnaire. Data were analyzed by univariate and bivariate analysis by Chi Square test. The results showed that most of the respondents had never received IVA Test counseling, as many as 69 respondents (70.4%). Almost half of the respondents have sufficient knowledge of the IVA Test, as many as 48 respondents (49%). The Chi Square test shows that there is a relationship between the provision of counseling and knowledge of the IVA Test (p value = 0.000). It is recommended to increase the provision of counseling programs about the IVA Test Keywords: Counseling, Knowledge, IVA Test